The Impact of the Financial Sector Development and Strengthening Law (UUP2SK) on the Supervision of Islamic Microfinance Institutions - Muhammad Farid Al-Azhar; Ahmad Zainul Abidin; Jafar Shiddiq; Syafiul Umam (ISTIFADA : Jurnal Ekonomi dan Lembaga Keuangan Syariah, 2026)
Islamic Microfinance Institutions (LMKS) play a crucial role in Indonesia's inclusive financial architecture, serving as a bridge for millions of unbanked and underbanked individuals to access Sharia-compliant financial products. However, their effectiveness and sustainability are often hampered by decades of dualism and fragmentation in the supervisory system. The enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UUP2SK) marks a fundamental turning point in Indonesia's financial sector supervisory architecture, including for LMKS. This study aims to comprehensively and in-depth analyze the impact of UUP2SK on the LMKS supervisory system. Using normative juridical research methods and a comparative approach, this study examines the shifting regulatory paradigm, shifting institutional authority, and the resulting multi-layered impacts on LMKS governance, risk management, and operations. The results show that UUP2SK significantly changes the supervisory landscape by shifting licensing and supervisory authority for cooperatives operating in the financial services sector, including the majority of LMKS, from the Ministry of Cooperatives and SMEs to the Financial Services Authority (OJK). This change introduces a new supervisory regime based on a risk -based supervision approach , the application of prudential principles, and increased demands for good corporate governance and strengthened consumer protection. While this reform promises long-term stability and increased public trust, its implementation faces multidimensional challenges related to the readiness of human resources on the regulatory and industry sides, technological infrastructure gaps, and the potential for increased compliance costs that could burden small-scale financial institutions (LMKS). This study recommends a proportional and adaptive implementation strategy, as well as collaborative synergy between regulators, industry associations, and academics to ensure an effective supervisory transition without harming the social mission and operational flexibility that are the core strengths of LMKS